THEORETICAL FOUNDATIONS OF SPEECH DEVELOPMENT OF PRESCHOOL CHILDREN (Academia Science Repository, 2023)
The process of developing speech and learning the native language is a complex and multifaceted phenomenon. A scientifically based methodology should be based on an understanding of both the essence and distinctive features of the language and the speech mechanism, knowledge of the patterns and features of the development of different aspects of speech, skills and abilities of verbal communication. Therefore, the theoretical basis of the methodology for the development of speech is made up of data from a number of sciences: physiology, theory of knowledge, psychology.